Screening Variables in Reducing the Brown Color from the Filtrate of Heavy Metal’s Elimination - Indrajati Kohar; Soediatmoko Soediman; Mario Mario; Deby Vinolia; Ni Nyoman Tri Puspaningsih; Leon Janssen (Fakultas Farmasi, Universitas Surabaya, 2016)
Heavy metals contamination is a major concern in the world, and also is in Indonesia. Manyattempts have been done to reduce or even eliminate it from the environment, among other ways theuse of agriculture waste, such as rice straw. Why use rice straw? Because it is available abundantly.Many studies showed that rice straw could adsorb heavy metals from polluted water, and it is cheap.The drawback of rice straw is the color of the filtrate is brown, so that it cannot be used for everydayor household purposes. An attempt using enzyme has been tried to reduce the brown color and it didreduce the brown color. Enzyme L-α-arabino-furanosidase is used in this study. However, as there aremany variables used in the experiments, before optimization can be conducted, a screening needs to becarried out first. Type of enzyme (optimum temperature of 50oC and 70oC), incubation time and amountof enzyme, number time of washing, water for washing, place of the rice plantation (high land and lowland), and size of straw, are the variables that need to be screened. The variables that gives the highestresponse in this study were enzyme-50, amount of enzyme : straw = 2 : 1 (10 ml of enzyme for each 5g of straw), 1 hour incubation time, amount of washing : 5 x 5 ml, place of plant: low land, and size ofstraw: ground. As for the type of washing liquid, both either demineralised water or Pb solution were thesame. However, the variables are still need to be reduced, and the experiment/study will be continuedto optimize the reduced variables.